Peran Pejabat Pembuat Akta Tanah dalam Proses Peralihan Jual Beli Hak atas Tanah - Murni, Christiana Sri (University of Jember, Indonesia, 2021)
The Land Deed Official (PPAT) is a public official granted the authority to make deeds of transfer of land rights, assignment of land rights, and authorization to impose mortgage rights according to the prevailing laws and regulations. However, the question arises about how significant the role of PPAT is in transferring the sale and purchase of land rights, considering the laws and regulations governing land sale and purchase are potentially irrelevant to the current situation. This study aims to analyze the role of PPAT in transferring the sale and purchase of land rights. This type of research is normative juridical research; by using a statutory approach and a conceptual approach. This study uses primary and secondary legal materials. Then, it is described and analyzed to answer the problem to clarify the role of PPAT. The study's results reveal that the process of transferring land rights can be carried out using customary law with three options, namely adol plas, adol gadai, and adol tahunan. Then, from the national law's perspective, land rights commerce must meet the material requirements and formal requirements. PPAT has an essential role in registering land data, namely by making evidence of legal actions regarding land plots. The PPAT position has a strategic role in making authentic deeds a requirement in transferring land rights due to sale and purchase. KEYWORDS: PPAT, Deed of Sale and Purchase, Transfer of Rights.